Комунікативно-прагматичні функції інверсії в англомовних прес-релізах - Козак, Світлана Володимирівна; Kozak, Svitlana V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Розглянуто таке явище англійської мови як суб’єктивність, а також засоби її вираження на синтаксичному рівні, а саме  інверсія. У зв’язку з неоднозначним трактуванням поняття, таке явище експресивного синтаксису стає одним із актуальних питань, яке вимагає додаткового дослідження. В умовах розвитку сучасної лінгвістики великої популярності набув напрям вивчення мови з погляду її впливу на читача. У роботі досліджено випадки інверсії, що сприяють переконанню слухача, та визначено основні функції та комунікативно-прагматичне призначення інверсії в англомовних прес-релізах. The notion of subjectivity in English and the means of its expression on different language levels and specifically on the syntactic one (namely inversion) are analyzed in the article. Word order is also an important means of expressing the actual division of the sentence. Usage of direct or inverted word order is predetermined by the speaker’s communicative tasks including the need to convey the message truly, to introduce special signals underlining new information and enhancing emotional and expressive meanings of sentences, to expand functional perspective in a progressive or regressive way. When we use invertion in a text it becomes more emphatic and emotional therefore influencing the reader more effectively and accurately reflecting the communicative strategy of the speaker trying to achieve a particular communicative goal.
Communicative and Pragmatic Functions of Inversion in English Press Release
Keywords: інверсія; inversion; тема; theme; рема; rheme